Integrating copy number data of 64 iAMP21 BCP-ALL patients narrows the common region of amplification to 1.57 Mb - Hormann, Femke M.; Hoogkamer, Alex Q.; Boeree, Aurélie; Sonneveld, Edwin; Escherich, Gabriele; den Boer, Monique L.; Boer, Judith M. (Frontiers in Oncology, 2023)
Background and purpose: Intrachromosomal amplification of chromosome 21 (iAMP21) is a rare subtype of B-cell precursor acute lymphoblastic leukaemia (BCP-ALL). It is unknown how iAMP21 contributes to leukaemia. The currently known commonly amplified region is 5.1 Mb. Methods: We aimed to narrow down the common region of amplification by using high resolution techniques. Array comparative genomic hybridization (aCGH) was used to determine copy number aberrations, Affymetrix U133 Plus2 expression arrays were used to determine gene expression. Genome-wide expression correlations were evaluated using Globaltest. Results: We narrowed down the common region of amplification by combining copy number data from 12 iAMP21 cases with 52 cases from literature. The combined common region of amplification was 1.57 Mb, located from 36.07 to 37.64 Mb (GRCh38). This region is located telomeric from, but not including, RUNX1, which is the locus commonly used to diagnose iAMP21. This narrow region, which falls inside the Down Syndrome critical region, includes 13 genes of which the expression of eight genes was significantly upregulated compared with 143 non-iAMP21 B-other cases. Among these, transcriptional repressor RIPPLY3 (also known as DSCR6) was the highest overexpressed gene (fold change = 4.2, FDR < 0.001) and most strongly correlated (R = 0.58) with iAMP21-related genome-wide expression changes. Discussion: The more precise definition of the common region of amplification could be beneficial in the diagnosis of iAMP21 based on copy number analysis from DNA sequencing or arrays as well as stimulate functional research into the role of the included genes in iAMP21 biology.